OCCUPATIONAL HAZARDS IN MINING AND MANUFACTURING SECTOR: AN ANALYSIS ON DISEASE CLAIMS IN MALAYSIA (UUM Journal of Legal Studies, 2014)
This paper examines the law regulating occupational illnesses or diseases suffered by workers at the work place. Its main focus is on the claims by workers to SOCSO for illness suffered or diseases contracted whilst performing their work or in the course of their employment. The main statute for compensation claim is Employees Social Security Act 1969 and the discussion will be made on the problem arising under section 28(1) and 28(4) of the 1969 Act. The issue involved is in establishing whether a correlation exists between the disease and the work performed by the workers. Such an issue could be the hindrance towards the success of such workers’ claims. Hence, this paper will explore the issue by analyzing statistics and decided court cases. The analysis of the court cases revealed that most of the claims were turned down when the claimants failed to show that the injury or death were the result of the employment. The author also suggests an alternative to have a scheduled and monitored occupational health check-up on the workers’ health to ensure whether any health problems occurs is due to the work.